The vaginal microbiome in HPV persistence and cervical cancer progression - Bautista, Jhommara; Altamirano-Colina, Adriana; López-Cortés, Andrés (Frontiers in Cellular and Infection Microbiology, 2025)
Persistent infection with high-risk human papillomaviruses (HR-HPV) is the primary cause of cervical cancer, but its progression depends on host and environmental factors beyond viral presence. The vaginal microbiome, particularly the transition from Lactobacillus crispatus–dominated communities to dysbiotic states enriched in Gardnerella, Fannyhessea, and Sneathia, has emerged as a key modulator of HPV persistence, local inflammation, and epithelial transformation. First, community state type IV (CST IV) microbiota strongly predict persistent HR-HPV infection and progression to high-grade lesions, highlighting their potential as non-invasive biomarkers for early risk stratification. Second, cervicovaginal dysbiosis alters mucosal immunity and promotes epigenetic reprogramming of both host and viral genomes, facilitating immune evasion and oncogenesis. Third, restoring Lactobacillus dominance through probiotics or microbial engineering holds translational promise for enhancing HPV vaccine efficacy and reducing cervical cancer burden. These findings position the vaginal microbiome not as a passive bystander, but as an active determinant of HPV-driven carcinogenesis and underscore its diagnostic and therapeutic potential in cervical cancer prevention.